2009
DOI: 10.1159/000223811
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis for Acute Kidney Injury: Techniques and Dose

Abstract: It has not been clearly shown which modality of dialysis is superior in the management of acute kidney injury (AKI). Most centers in developed countries have adopted extracorporeal blood purification (EBP) strategies, such as continuous or intermittent forms of hemodialysis or hemofiltration, for the supportive management of AKI. On the other hand, the use of peritoneal dialysis (PD) is widespread in developing countries in view of its ease of use, low cost and minimal requirements on infrastructure. The dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 20 publications
4
23
0
3
Order By: Relevance
“…Most of the patients had their catheter removed and dialysis method changed, because no success was obtained with the treatment. The main mechanical complication was early leakage (10%), which is in agreement with other studies (6,9,11,29).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Most of the patients had their catheter removed and dialysis method changed, because no success was obtained with the treatment. The main mechanical complication was early leakage (10%), which is in agreement with other studies (6,9,11,29).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are similar to the results of previous studies that showed that PD clearance was limited by dialysate flow, membrane permeability, and area (6)(7)(8)(9)(10)(11)(20)(21)(22)(23)(24)(25)(31)(32)(33)(34)(35). A 2-L exchange with a dwell time of 30 minutes can achieve dialysate saturation of around 50%.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations